OPTIMALISASI PROSES INBOUND MELALUI PENERAPAN LEAN LOGISTICS DI WAREHOUSE FMCG PADA PT DE - Shafalah, Fikry; Permana, Tatang; Larutama, Wiku (Program Studi Teknik Industri Universitas Teknologi Sumbawa, 2025)
A slow and inefficient inbound process is a major challenge in the warehouse operations of PT DE, a company in the FMCG sector. This study aims to optimize the inbound process through the implementation of Lean Logistics. The method used is a quantitative approach by combining Lean Six Sigma through the DMAIC cycle and Kaizen principles through the PDCA cycle. Observations show that most inbound activities fall under Necessary Non-Value Added (NNVA), such as manual inspections, data entry, and documentation, accounting for up to 93% of the total process duration. Root cause analysis was carried out using Value Stream Mapping and Fishbone Diagram. Improvement solutions include implementing barcode/RFID technology, automated conveyors, employee training, and standardized procedures. After implementation, there was a significant increase in the speed and accuracy of goods receipt. Control was maintained through regular audits and a digital monitoring system. The application of Lean Logistics proved effective in reducing waste, increasing efficiency, and supporting continuous improvement in the FMCG warehouse environment